Spectrophotometric analysis of artesunate injections availablein community pharmacies in Northern and Western Uganda - Ayogu, Ebere Emilia; Ngolryeko, Emmanuel Aryon; Ezeonwumelu, Joseph Obiezu Chukwujekwu; Wawata, Ibrahim Garba; Sadiq, Bashir Olaniyi (Taylor & Francis group, 2025)
The surge in different brands of artesunate injection in Uganda, has raised the need for this study, which aimed at quantifying the actual amount of artesunate in different brands of artesunate injections available in Northern and Western Uganda.AIMThe surge in different brands of artesunate injection in Uganda, has raised the need for this study, which aimed at quantifying the actual amount of artesunate in different brands of artesunate injections available in Northern and Western Uganda.The wavelength at maximum absorbance of pure artesunate powder was determined using Ultraviolet-visible spectrophotometer and Beer Lambert's plot was generated. This was validated and used to assay 27 brands of artesunate.MATERIALS AND METHODSThe wavelength at maximum absorbance of pure artesunate powder was determined using Ultraviolet-visible spectrophotometer and Beer Lambert's plot was generated. This was validated and used to assay 27 brands of artesunate.In the spectrophotometric assay method used, Beer Lambert's law was obeyed within the range of 20 µg/ml-140 µg/ml with linear regression equation of y = 0.012 + 0.030 and correlation coefficient of (R2) 0.999 (n = 9). The limits of detection (sensitivity) and quantification were found to be 0.83 mg/ml and 2.09 mg/ml respectively. About 66.6% (18) and 33.3% (9) had actual artesunate content higher and lower than labeled claim respectively, while 40.7% (11) had deviations from labeled claim that were within acceptable limits.RESULTSIn the spectrophotometric assay method used, Beer Lambert's law was obeyed within the range of 20 µg/ml-140 µg/ml with linear regression equation of y = 0.012 + 0.030 and correlation coefficient of (R2) 0.999 (n = 9). The limits of detection (sensitivity) and quantification were found to be 0.83 mg/ml and 2.09 mg/ml respectively. About 66.6% (18) and 33.3% (9) had actual artesunate content higher and lower than labeled claim respectively, while 40.7% (11) had deviations from labeled claim that were within acceptable limits.Most brands of artesunate injection assayed deviated from labeled claim, regional/environmental factor impacted much on the stability of artesunate thus there is need for further screening of the quality of artesunate injection in circulation in view of the therapeutic consequences of substandard artesunate injection.CONCLUSIONMost brands of artesunate injection assayed deviated from labeled claim, regional/environmental factor impacted much on the stability of artesunate thus there is need for further screening of the quality of artesunate injection in circulation in view of the therapeutic consequences of substandard artesunate injection. MEDLINE - Academic